A systematic literature review on the decarbonisation of the building sector—a case for Nigeria - Abam, Fidelis Ibiang; Nwachukwu, Chinedum Oscar; Emodi, Nnaemeka Vincent; Okereke, Chukwumerije; Diemuodeke, Ogheneruona E.; Owolabi, Abdulhameed Babatunde; Owebor, Kesiena; Suh, Dongjun; Huh, Jeung-Soo (Frontiers in Energy Research, 2023)
The buildings sector is responsible for over 36 % of total global end-use energy utilization and nearly 40 % of the total indirect and direct carbon emissions. Low-carbon or zero-energy buildings remain the only option to lessen the sector's energy consumption and CO2 emissions. The current systematic study examines low-carbon buildings under deep decarbonization scenarios in selected global south regions from 2010 to 2021. The study was channelled by the PRISMA ('Preferred Reporting Items for Systematic reviews and Meta-Analyses') review process, which identified 29 related articles from Scopus, Web of Science., and Google Scholar databases. The identified critical drivers of emissions were population, gross domestic product, dwelling characteristics, and urbanization. The dwelling characteristics contributed about 12 % and 27 % to the total CO2 emissions in the selected regions. The population varies between 23 and 27 % across the areas. Specific findings were made for inclusion in the Nigeria model while the general results were observed and further studies proposed. Total investment from the private and public sectors was identified as key to achieving the transition process of decarbonization in the building sector.